2009
DOI: 10.4049/jimmunol.0901639
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity against Fibrinogen Mediates Inflammatory Arthritis in Mice

Abstract: Rheumatoid arthritis (RA) is an autoimmune synovitis characterized by the presence of anticitrullinated protein Abs, although the exact targets and role of anticitrullinated protein autoimmunity in the pathogenesis of RA remain to be defined. Fibrinogen, which can be citrullinated, has recently emerged as a candidate autoantigen. To determine whether autoimmunity against fibrinogen can mediate inflammatory arthritis, we immunized a variety of common mouse strains with fibrinogen and found that DBA/1 and SJL mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 50 publications
1
50
1
Order By: Relevance
“…Multiple studies have directly implicated the primary fXIIIA substrate fibrin(ogen) in the pathogenesis of inflammatory arthritis. 8,[21][22][23][24] These data also support the concept that fXIIIA contributes to arthritis pathogenesis through distinct fibrinogen-dependent inflammatory processes and through altered osteoclast function-mediated mechanisms.…”
Section: Discussionsupporting
confidence: 75%
“…Multiple studies have directly implicated the primary fXIIIA substrate fibrin(ogen) in the pathogenesis of inflammatory arthritis. 8,[21][22][23][24] These data also support the concept that fXIIIA contributes to arthritis pathogenesis through distinct fibrinogen-dependent inflammatory processes and through altered osteoclast function-mediated mechanisms.…”
Section: Discussionsupporting
confidence: 75%
“…With an increased understanding of their potential role in disease pathogenesis, citrullinated proteins have been evaluated as immunogens in the presence of FCA [4][5][6]13]. These studies showed that there was a slight increase in immune responses towards the injected immunogen, and a slight increase in joint damage reflected in the ankle.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade autoantibodies to citrullinated protein antigens (ACPA) and/or peptides have been used as diagnostic tools and have been implicated in the disease process [1]. A number of citrullinated proteins have been implicated as playing a central role in disease pathogenesis; including, filaggrin, fibrin, fibrinogen, vimentin, alpha enolase, collagen, and even peptidylagrinine deiminase (PAD), the enzyme responsible for the post-translational modification of arginine into citrulline [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have provided evidence that fibrinogen plays a multifaceted role in inflammatory responses and autoimmunity. 18,19 The ability of fibrinogen to participate in the inflammatory response depends on its specific interaction with integrins, the leukocyte cell surface adhesion receptors. M2 (CD11b/CD18, Mac-1) and X2 (CD11c/CD18, p150,95) are the main fibrinogen receptors and are expressed on neutrophils, monocytes, macrophages and several subsets of lymphocytes.…”
Section: Becatti Et Al Role Of Neutrophils In Thrombus Formation 303mentioning
confidence: 99%